Development Perspectives for Georgian Regional Media Schools Under Conditions of Digital Divide - Shamilishvili, Manana; Tkhilava, Eka; Shamilishvili, Inga (Technium Social Sciences Journal, 2025)
On the basis of the qualitative research conducted on the basis of several regional and central Georgian universities, the article presents the development prospects of media schools and alternative models for Georgian regional media schools. Results of the research showed that regional university education in the direction of digital media in Georgia is in a critical state, suffering from forms of inequality, both in terms of educational bases and human professional resources. As a result, young people choose central universities, which creates unequal opportunities for the development of the regional parts of Georgia. The situation of regional universities is becoming even more problematic; in the research, we tried to show that this process will bring disastrous results for the whole country if there is no professional distribution, redistribution of media students across the country and purposeful stratification of intellectual resources.